2013
DOI: 10.1186/cc12878
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dental plaque following hospitalisation in a critical care unit: an observational study

Abstract: IntroductionPrevious research has suggested that deterioration in oral health can occur following hospitalisation. The impact of such deterioration could increase the risk of oral disease, reduce quality of life and increase the potential for healthcare-associated infections (HCAI) such as healthcare-associated pneumonia (HAP). However, the strength of the evidence is limited by, amongst other factors, the few observational studies published that assess oral health longitudinally. In view of the microbiologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
30
0
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 28 publications
3
30
0
8
Order By: Relevance
“…38 However, there is considerable variability among critical care nurses on how oral care is delivered, with many choosing a foam swab in preference to a toothbrush, or neither method being used and relying on the application of antiseptic solutions or gels 1839 40 Almost all studies in critically ill patients have demonstrated that plaque scores increase even when oral care programmes are in place4 7–9 and it is therefore important to determine the optimal approaches to reduce plaque scores in mechanically ventilated patients 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…38 However, there is considerable variability among critical care nurses on how oral care is delivered, with many choosing a foam swab in preference to a toothbrush, or neither method being used and relying on the application of antiseptic solutions or gels 1839 40 Almost all studies in critically ill patients have demonstrated that plaque scores increase even when oral care programmes are in place4 7–9 and it is therefore important to determine the optimal approaches to reduce plaque scores in mechanically ventilated patients 14…”
Section: Discussionmentioning
confidence: 99%
“…7–9 A number of interventions aimed at improving oral cleanliness have demonstrated a reduction in VAP or mortality in randomised clinical trials 10–13. However, these trials did not actually measure oral cleanliness and there has been a paucity of research conducted in mechanically ventilated patients on what represents the optimal methods for improving oral hygiene 14.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 In addition, patients at intensive care units (ICUs) frequently exhibit poor oral hygiene, with substantial increase of the oral biofilm. 10 Ventilator-associated pneumonia (VAP) is an important cause of morbidity and mortality in ICUs. 11,12 Recent studies have suggested that VAP may be associated with microbial colonization of dental plaque and oropharynx; however, these evaluations were conducted with different methodologies and attained no conclusive results.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Significant levels of Staphylococcus aureus, Klebsiella pneumoniae and Enterobacter cloacae have also been found in the dental biofilm of ICU patients. 10 Due to the diversity of pathogens detected in the oral biofilm of patients with VAP, it is important to investigate which respiratory pathogens can colonize the oral biofilm of intubated patients in ICUs. Thus, the aim of this study was to explore possible associations between respiratory pathogens from tracheal aspirate and oral biofilm in intubated patients in an ICU and to identify the most common respiratory pathogens present in the oral biofilm, particularly in patients that develop VAP.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation